Emotional Rhetoric In Political Discourse: Analyzing President Bush's Speeches On The Iraq War Through Chilton's Emotional Theory - Hameed Rasheed, Mohammed (International Journal on Integrated Education, 2025)
This study critiques President Bush’s speeches on the Iraq war and terrorism through the lens of Chilton's emotional theory, highlighting the complex relationship between language emotion and politically persuasive belief. The study, which deconstructed five significant speeches between 2001 and 2003, reveals how Bush used emotional rhetoric to stir public sentiment and justify military action. Using a rigorous approach to discourse analysis, the study identified eight vital emotional components, such as fear of attack and safety. It showed. It showed that 59% of the sentences analyzed were designed to evoke specific emotional responses. The findings underscore the strategic use of language in political discourse, demonstrating how emotional manipulation serves as a means to influence public opinion and legitimize the legitimacy of controversial policies. Moreover, Political speech is a powerful linguistic tool in world politics that can identify the destiny of countries under the conditions of war. Therefore, it is worth investigating the strategies that politicians apply in their political speeches to achieve their political goals. This study critically examines President Bush's speech on the Iraq war and terrorism through Chilton's emotional theory. The study shows that political discourse is not just a means for information but a powerful tool for shaping public sentiment and guiding decision-making. Using emotional language, Bush effectively instilled feelings of fear and belief that were critical to winning public support for military action. The dominant themes of lingering memories of 11 served to incite fear, while assertions about American military strength and security boosted confidence.